Nutritional habits in Spanish female students of childbearing age - María Teresa Iglesias-López; Ana Abreu; Juan Diego Ramos-Pichardo; Elia Fernández Martínez (Journal of King Saud University: Science, 2023)
Aim: To analyse the dietary habits, alcohol consumption, healthy eating index and student performance of a sample of students at a Spanish university to determine if their intake of nutrients reach optimal levels for fertility. Methods: Descriptive cross-sectional study of female university students in Madrid, data were collected in Nutrition classes. Participants were 470 women nursing studying at a private university in Madrid, non-random sample was used. An AUDIT test was conducted to determine alcohol consumption. Habits and dietary assessment with a three-day record using DIAL® program to know main nutrients intake. Quantitative variables appeared as mean ± standard deviation, adjusted for all pairwise comparisons using the Bonferroni correction Statistical analysis was performed using SPSS 25®. Results: The majority of the Spanish university women of reproductive age participating in the study did not have the recommended intake of some macro and micronutrients carbohydrates, vitamins D and B9, Mg, Fe, and I. Conclusions: This study opens further lines of research. It is necessary to carry out qualitative research into students’ self-perception and their dietary and sleeping habits. Addressing ways to improve food access, dietary quality, and healthy lifestyle, should be focused on future intervention programs and policies for college students.